2009
DOI: 10.1128/aac.00460-09
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Assessment of Nevirapine and Metabolites in Human Immunodeficiency Virus Type 1-Infected Patients with Hepatic Fibrosis

Abstract: Nevirapine is a nonnucleoside reverse transcriptase inhibitor used as part of combination therapy for human immunodeficiency virus (HIV) infection. Nevirapine may be prescribed for patients with hepatic fibrosis and cirrhosis. Significant autoinduction of cytochrome P450 3A4 and 2B6 following multiple dosing prompted an assessment of the metabolic profiles in patients with liver disease receiving chronic nevirapine therapy. HIV-infected patients with hepatic fibrosis who were receiving a stable antiretroviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…In agreement with others, no relationship between nevirapine clearance and weight was evidenced (11,22). No modification in nevirapine pharmacokinetics was seen in patients with liver disease (8,11), and no relationship between ALAT and nevirapine concentrations was found in the present study.…”
Section: Discussionmentioning
confidence: 39%
“…In agreement with others, no relationship between nevirapine clearance and weight was evidenced (11,22). No modification in nevirapine pharmacokinetics was seen in patients with liver disease (8,11), and no relationship between ALAT and nevirapine concentrations was found in the present study.…”
Section: Discussionmentioning
confidence: 39%
“…Our plasma samples were not hydrolyzed; therefore, the plasma ratio of hydroxynevirapine to its glucuronide is not available in our study. A comparison of steadystate trough plasma concentrations in our patients with concentrations measured in HIV-infected patients with mild liver fibrosis (13) showed that nonconjugated 2-hydroxynevirapine and 3-hydroxynevirapine concentrations are well below those of the glucuronides, which remained lower than those of nevirapine, roughly 2 ng/ml versus 177 ng/ml and 12 ng/ml versus 759 ng/ml, respectively. In contrast, 8-hydroxynevirapine and 12-hydroxynevirapine concentrations are closed whether plasma was hydrolyzed or not (29 versus 31 ng/ml and 504 versus 142 ng/ml, respectively), indicating that glucuronide concentrations of these metabolites in plasma are low.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites are eliminated in the urine as conjugates, mainly glucuronides (14). Relatively little is known regarding nevirapine biotransformation and metabolite disposition following a single dose and at steady state, in part due to the lack of a direct and sensitive assay (13,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strong correlations were observed between 2-OH NVP and nevirapine concentrations while 3-OH NVP and nevirapine demonstrated weak correlations. In a study to assess the pharmacokinetics of nevirapine and metabolites in patients with hepatic fibrosis, the metabolite profiles were comparable across the stages of the disease (11). Risk of virological failure increased 5-fold when nevirapine concentrations were below 3 mg/L and dose adjustment has been suggested if the nevirapine Cmin is lower than 3 mg/L (12,13).…”
Section: Discussionmentioning
confidence: 99%